Rachunek kosztów docelowych jako narzędzie analizy inwestycji w rolnictwie - Mielcarek, Jarosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The expression development for free cash flows to firm taking into account the flat-rate tax on special branches of agricultural production was necessary to use the target costing for the analysis of agricultural investment project. It made possible to present essential for this costing the appropriately changed formula for target minimum rate of return on sales therefore. The modified current unit cost for investment project was lower than the allowable cost. Discount criteria for acceptance of this project were fulfilled. The size of the safety margin and safety margin rate for current costs reached a level indicating a low risk of failure of the project.